Contact Tracing and Profile of Lassa Fever Contacts in Edo State, Nigeria: Implications for the Control of Lassa Fever Outbreaks - Faith Ireye (Journal of Health Sciences and Surveillance System, 2021)
Background Edo State has recorded recurrent Lassa fever (LF) outbreaks in the past and had the highest proportion of confirmed cases in Nigeria in 2018. The aim of this study was to profile Lassa fever contacts and demonstrate the implications of contact tracing in the control of the disease. Methods This is a cross-sectional study which was based on secondary analysis of information derived from Lassa fever contact tracing forms used during the response to the LF outbreak of 2018 in Edo State. Contact tracing and data management were part of WHO’s support to the State. Using SPSS, associations and other relationships between selected variables were tested. The significance level was set at p< 0.05. Results Total contacts followed up were 2527 during the period under consideration. Higher mean contacts per case (CPC) was significantly associated with contacts in Edo South, with contacts of cases that died and with cases with symptomatic contacts (F= 8.307, p<0.001; t= 14.995, p<0.001; t= 6.161, p= 0.014 respectively). Following the integration of contact tracing with awareness campaigns, the number of newly diagnosed cases per week dropped from over 30 in the 7th week to 2 in the 13th week (42 days or 2 incubation periods). Conclusion Effective contact tracing contributed significantly to the identification of symptomatic contacts and to rapid control of the 2018 Lassa fever outbreak in Edo State. We recommend the deployment of effective contact tracing in the control of outbreaks of viral haemorrhagic fevers especially Lassa fever.